Internet of Things for Remote Healthcare - Mishra, PK; Pradhan, MR; Panda, M (International Journal of Computer Sciences and Engineering, 2025)
IoT is a innovative innovation which bridges interoperability challenges to radically change the way in which healthcare will be delivered, driving better outcomes, increasing efficiency and making healthcare affordable. Industry analysts predict that the ability for patients to take more responsibility of their health and the promotion of preventive measures are capable of disrupting current care delivery and will shape the future of healthcare. In this paper, we discuss today´s issues, including benefits and difficulties, as well as approaches to find a way the problems of employing and integrating Internet of Things devices in healthcare systems. It proposes few applications of IoT in rural healthcare and ways to improve primary health needs of the developing nations.